Korean adolescents’ coping strategies on self-harm, ADHD, insomnia during COVID-19: text mining of social media big data - Do, Ryemi; Kim, Soyeon; Lim, You Bin; Kim, Su-Jin; Kwon, Hyerim; Kim, Jong-Min; Lee, Sooyeon; Kim, Bung-Nyun (Frontiers in Psychiatry, 2023)
Introduction: Since the Coronavirus disease 2019 (COVID-19), public safety measures, including social distancing and school closures, have been implemented, precipitating psychological difficulties and heightened online activities for adolescents. However, studies examining the impact of the pandemic on adolescent mental health and their coping strategies in Asian countries are limited. Further, most studies have used survey measures to capture mental health challenges so far. Accordingly, this study aimed to examine the psychological challenges South Korean adolescents experienced and their coping strategies during the pandemic using the Natural Language Processing (NLP). Text Mining (TM) technique on adolescents’ social media texts/posts. Method: The data were gathered from social media texts/posts such as online communities, Twitter, and personal blogs from January 1, 2019, to October 31, 2021. The 12,520,250 texts containing keywords related to adolescents’ common psychological difficulties reported during the pandemic, including self-harm, Attention-Deficit/Hyperactivity Disorders (ADHD), and insomnia, were analyzed by TM, NLP using information extraction, co-occurrence and sentiment analysis. The frequency of the keywords and their associated words every month was also analyzed to understand the time trend. Results: Adolescents used the word “self-harm” in their social media texts more frequently during the second wave of COVID-19 (August to September 2020). “Friends” was the most associated word with “self-harm.” While the frequency of texts with “Insomnia” stayed constant throughout the pandemic, the word “ADHD” was increasingly mentioned in social media. “Insomnia” was most frequently associated with ADHD medications and sleeping pills. Friends were generally associated with positive words, while parents were associated with negative words. Conclusion: During COVID-19, Korean adolescents often expressed their psychological challenges on social media platforms. However, their coping strategies seemed less efficient to help with their difficulties, warranting strategies to support them in the prolonged pandemic era. For example, Korean adolescents shared psychological challenges such as self-harm with friends rather than their parents. They considered using medicine (e.g., sleeping pills and ADHD medication) as coping strategies for sleep and attention problems.